2012
DOI: 10.3109/03009742.2012.697189
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of vitamin D deficiency in non-supplemented women with systemic lupus erythematosus in the Mediterranean region: a cohort study

Abstract: Vitamin D insufficiency is highly prevalent among SLE patients, even in southern regions. Sunscreen use and obesity increase the risk. Clinicians should be aware of these factors and supplement SLE patients at risk of vitamin D deficiency accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 14 publications
5
29
2
Order By: Relevance
“…However, no significant correlation was found between vitamin D insufficiency and deficiency with bone loss. In our previous study, daily sunscreen use and high BMI were the main predictors of vitamin D deficiency [19]. as we mentioned before, we found a statistically significant correlation between low BMI and low BMD.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, no significant correlation was found between vitamin D insufficiency and deficiency with bone loss. In our previous study, daily sunscreen use and high BMI were the main predictors of vitamin D deficiency [19]. as we mentioned before, we found a statistically significant correlation between low BMI and low BMD.…”
Section: Discussionsupporting
confidence: 81%
“…It is well known that Sle patients show reduced 25-OH-vitamin D levels compared with general population [16,19]. Many factors are related to this (HcQ use, sunscreen, and renal involvement).…”
Section: Discussionmentioning
confidence: 99%
“…1 2 Studies within patients with SLE indicate that lower 25[OH]D levels may correlate with increased disease activity, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] although inconsistently. [17][18][19][20][21][22][23][24] Variation within the vitamin D receptor gene (VDR), the vitamin D receptor protein that binds the active form of vitamin D, 1,25-dihydroxyvitamin D (1,25[OH] 2 D), has been associated with higher SLE disease activity in females 25 and higher damage score. 26 Whether vitamin D is related to risk of developing SLE has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…While the specific questions used were not individually validated against adolescent plasma 25(OH)D, previous studies have suggested a positive association between plasma vitamin D and lighter skin, [13] less frequent sunscreen use, [14] [15] and tanning bed use [16] and we hypothesize that girls with more frequent sunburns are likely to have greater vitamin D exposure. We asked participants about the color of their untanned skin (very fair, fair, olive, or dark).…”
Section: Methodsmentioning
confidence: 99%